2020
DOI: 10.1111/ffe.13254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of jig constraint state during welding process on fatigue properties of Al/CFRP dissimilar welds and fatigue life evaluation based on singular stress

Abstract: Manufacturers have been promoting multimaterial designs. So the dissimilar material welding methods are being developed. Especially, heat welding technology, which is a direct joining by local heating, has been focussed. Therefore, this study used a heat welding technology for friction stir spot welding of aluminium alloy and carbon fibre‐reinforced plastic. This study investigated the effect of changes to jig constraint of joined members on the fatigue properties of joints. Also, the fatigue life estimation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[45][46][47] Welding techniques are also used for the dissimilar assemblies. [48][49][50] Compared to these conventional methods, direct bonding has been considered as an effective way to manufacture metal/polymer structures. [51][52][53] Among direct joining methods, hot pressing has emerged as an outstanding alternative.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47] Welding techniques are also used for the dissimilar assemblies. [48][49][50] Compared to these conventional methods, direct bonding has been considered as an effective way to manufacture metal/polymer structures. [51][52][53] Among direct joining methods, hot pressing has emerged as an outstanding alternative.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, current research has shown experimental setups for the very high cycle regime (VHCF) by use of selected composite systems 25 or functional hybrid materials in the purpose of structural health monitoring (SHM) 26 . Fatigue properties of hybrid aluminum/CFRP joints have been investigated in recent research as an alternative to the riveting process such as electromagnetic riveting 27 or the use of self piercing rivets 28 as well as friction stir spot welding 29 . Experimental investigations of the fatigue properties of ultrasonically welded aluminum/FRP joints are lacking to a large extent in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…26 Fatigue properties of hybrid aluminum/CFRP joints have been investigated in recent research as an alternative to the riveting process such as electromagnetic riveting 27 or the use of self piercing rivets 28 as well as friction stir spot welding. 29 Experimental investigations of the fatigue properties of ultrasonically welded aluminum/FRP joints are lacking to a large extent in the literature.…”
Section: Introductionmentioning
confidence: 99%